Anti-Obesity Effect of Dictyophora indusiata Mushroom Polysaccharide (DIP) in High Fat Diet-Induced Obesity via Regulating Inflammatory Cascades and Intestinal Microbiome - Kanwal, Sadia; Aliya, Shams; Xin, Yi (Frontiers in Endocrinology, 2020)
Obesity is a multifactorial metabolic disorder characterized by low-grade chronic inflammation, hyper-permeability of the gut epithelium, and perturbation of the intestinal microbiome. Despite the numerous therapeutic efficacies of Dictyophora indusiata mushroom, its biological activity in alleviating obesity through regulation of gut microbiota and inflammatory cascades remain obscure. Henceforth, we determined the modulatory impact of D.indusiata polysaccharide (DIP) in the high-fat diet (HFD) induced obesity mice model. The experimental subjects (BALB/C mice) were supplemented with chow diet (Control group), high-fat diet (HFD group), or HFD along with DIP at a low dose (HFD+DIP(L) and high dose (HFD+DIP(H). Obesity-related parameters, including body weight gain, epididymal adipocytes size, fat accumulation, adipogenic markers, lipogenic markers, inflammatory associated markers, intestinal integrity, and intestinal microbiome, were elucidated. Our findings demonstrated that the oral administration of DIP at low dose partially and at high dose significantly reversed HFD induced obesity parameters. Furthermore, the body weight, fat accumulation, adipocytes size, adipogenic and liver associated markers, glucose levels, inflammatory cytokines, and endotoxin (Lipopolysaccharide, LPS) levels were reduced considerably. Moreover, the study revealed that DIP treatment reversed the dynamic alterations of the gut microbiome community by decreasing the Firmicutes to Bacteroidetes ratio. These findings led us to infer the therapeutic potential of DIP in alleviating HFD induced obesity via regulating inflammatory cascades, modulating intestinal integrity, and intestinal microbiome community.